Cross-Talk between the Aeromonas hydrophila Type III Secretion System and Lateral Flagella System - Zhao, Yu-Hang; Shaw, Jonathan G. (Frontiers in Microbiology, 2016)
Aeromonas hydrophila is responsible for aeromonad septicaemia in fish, and gastroenteritis and wound infections in humans. The type III secretion system (T3SS) is utilized by aeromonads to inject protein effectors directly into host cells. One of the major genetic regulators of the T3SS in several bacterial species is the AraC-like protein ExsA. Previous studies have suggested a link between T3SS regulation and lateral flagella expression. The aim of this study was to determine the genetic regulation of the T3SS and its potential interaction with the lateral flagella system in A. hydrophila. To investigate this the genes encoding the T3SS regulatory components exsA, exsD, exsC and exsE were mutated and the activities of the T3SS promoters were measured in wild-type and mutant backgrounds demonstrating a regulatory network. The Exs proteins were shown to interact with each other by BACTH assay and Far-Western Blot. The findings suggested a regulatory cascade in which ExsE was bound to the chaperone protein ExsC. When ExsC was free it sequestered the anti-activator ExsD thus stopping the inhibition of the T3SS master regulator ExsA allowing T3SS expression. The T3SS regulatory components were also shown to affect the expression of the lateral flagella system. The activities of the lateral flagella promoters were shown to be repressed by the absence of ExsD and ExsE, suggesting that the T3SS master regulator ExsA was a negative regulator of the lateral flagella system.